ANALISIS HUKUM PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE TERHADAP TANTANGAN DAN SOLUSI NORMATIF DI INDONESIA - Dwi Dasa Suryantoro (Universitas Nurul Jadid, 2025)
This research aims to analyze the form of consumer legal protection in e-commerce transactions in Indonesia and identify new challenges that arise in its implementation in the midst of the rapid development of the digital market. The method used is a normative juridical approach with an analysis of laws and regulations, legal doctrines, and relevant literature studies from scientific journals in the last ten years. The results of the study show that consumer legal protection is still fragmentary and has not been fully adaptive to the dynamics of digital transactions, especially in terms of business actors' responsibilities, personal data protection, and online dispute resolution mechanisms. Weaknesses in the national legal system are also exacerbated by the low digital literacy of consumers and the ineffective supervision and enforcement of the law by the competent authorities. This study concludes that regulatory reform is needed through harmonization with international legal instruments, strengthening community-based consumer legal education, and applying the principles of fairness and transparency in digital regulations. These findings are expected to be a reference in formulating consumer protection policies that are more adaptive, sustainable, and inclusive in the digital economy era.